2013
DOI: 10.1093/inthealth/iht027
|View full text |Cite
|
Sign up to set email alerts
|

Trachoma among children in community surveys from four African countries and implications of using school surveys for evaluating prevalence

Abstract: Estimating the prevalence of trachoma through examination of only school-going children risks underestimating the true prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
2
16
1
Order By: Relevance
“…Published data from studies in Ethiopia [50], Niger [50], Tanzania [18], Gambia [18], Cameroon [48], Mali [51] and Brazil [52] indicate that in other trachoma-endemic populations, the highest age-specific TF prevalence is generally in those aged 3–4 years. When published age-specific TF profiles from other parts of the world are compared to the age distribution in this study (Fig 5), the peak age-specific TF prevalence in our data is shown to be in an older age group.…”
Section: Resultsmentioning
confidence: 99%
“…Published data from studies in Ethiopia [50], Niger [50], Tanzania [18], Gambia [18], Cameroon [48], Mali [51] and Brazil [52] indicate that in other trachoma-endemic populations, the highest age-specific TF prevalence is generally in those aged 3–4 years. When published age-specific TF profiles from other parts of the world are compared to the age distribution in this study (Fig 5), the peak age-specific TF prevalence in our data is shown to be in an older age group.…”
Section: Resultsmentioning
confidence: 99%
“…Infants also cannot cooperate with the eye examination and conjunctival secretion sample collection. An African study suggested that school surveys might underestimate the prevalence because differences were found between those who attended school and those who did not; however, in Nigeria where school attendance is high the differences were not seen [38, 39]. As the rate of school attendance is high in the Shanghai migrant school aged children the prevalence in our study may be fairly accurate.…”
Section: Discussionmentioning
confidence: 54%
“…C. trachomatis remains an epidemic in various countries, and Canada is the only high-income country with a trachoma prevalence of >5% (Shattock et al, 2015). Active trachoma exists in a number of areas in Asia and Africa and other developing countries (Last et al, 2014;King et al, 2013;Nigusie et al, 2015;Burton et al, 2010), and a great number of studies have shown C. trachomatis serotypes differ across regions. For 8 .…”
Section: Discussionmentioning
confidence: 99%